PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI JERUK SOKSOK 2 DENGAN MENGGUNAAN MEDIA GAMBAR : SD NEGERI JERUK SOKSOK 2 - MURHASIN MURHASIN (Mitra Pendidikan, 2021)
The objectives of this classroom action research are as follows: 1) To determine the improvement of student learning outcomes using image media 2) To see the activities of students in improving the learning outcomes of class II SD Negeri Jeruk Sosok 2. This type of research is classroom action research because the research was conducted to solve problems in the classroom. The procedure in this classroom action research was carried out in 2 cycles. Each cycle consists of four stages of activity, namely the first stage of planning, the second stage of implementation, the third stage of observation, and the fourth stage of reflection. The subjects in this study were 24 students of grade II SD Negeri Jeruk Sosok 2 as many as 24 students. The data collection techniques used in this study were observation and tests. The data analysis technique used is quantitative analysis. Based on the results of classroom action research and the discussion that has been described, it can be concluded that learning with the use of image media can improve the mathematics learning outcomes of grade II students of SD Negeri Jeruk Sosok 2 in the semester of the 2017/2018 academic year.